Analysis growth of MSME’s through sustainable development goals, entrepreneurship development, and digital financial reports - Ibnu Austrindanney Sina Azhar; Taufik Akbar Parluhutan; Mutia Ismai; Yuni Lestari Br Sitepu; Ikhwan Nurhadi (Jurnal Mantik, 2023)
The main function of sustainable development is one of the important abilities and skills needed by msme’s business actors to manage their finances and achieve the best business performance. The aim of this research is to analyze the impact of sustainable development and entrepreneurship development on the growth of msme’s in the city of Medan mediated by digital financial reports. This research uses a quantitative descriptive method with an explanatory research approach. data was obtained from a sample of 100 business actors in Medan city. The data analysis technique used is structural equation modeling – partial least squares (sem-pls). The research results show that the sustainable development goals, entrepreneurship development and digital financial reports influence the growth of msme’s in Medan city. Digital financial reports do not mediate the influence of the sustainable development goals and entrepreneurship development on the growth of msme’s in Medan city. The novelty of this research is its accuracy in providing information to stakeholders regarding the importance of sustainable development goals for msme’s business actors. therefore, stakeholders must strive to provide education to msme’s business actors about the importance of the sustainable development goals